The Influence of Mathematical Thinking Ability with Modified MOORE Method on Learning Outcomes of Basic Mathematic II Chemical Education Students - Heleni, Susda; Zulkarnain, Zulkarnain (Journal of Educational Sciences, 2018)
Developing the ability of absolute thinking is needed inmathematic class where the subject has a characteristic as a branch ofscience which the object of study is abstract-natured and related with apattern of thinking. Basic mathematics is one of the courses that can developstudent’s ability to think. The results acquired by the students are still notmaximized; this is because the students struggle to develop their ownknowledge to form concepts. Student’s activities in the learning process areonly skill-natured in solving problems. One of the learning methods that canbe implemented is the Modified Moore method. This research aims todiscover the effects of mathematical thinking capabilities with the ModifiedMoore Method towards the learning achievement of Basic Mathematic II ofChemistry study program from the FKIP of Universitas Riau in the evensemester of 2013/2014 academic year. The form of this research is a quasiexperimentalresearch. The experiment design used in this research is theSingle Group Pretest/Posttest Design which includes Quasi ExperimentalDesign without control group. The population in this research is the studentsof Chemistry  study program from the FKIP of Universitas Riau in the evensemester of 2013/2014 academic year. The sample of this research is allstudents of Chemistry study program from the FKIP of Universitas Riau  inthe even  semester of 2013/2014 academic year consisting 36 peoples. Thesample is obtained through purposive sampling technique. Based on dataanalysis using t test on mathematical thinking capabilities by applyingmodified Moore Method, it was found that  students scores during post testis better than pre-test. The influences of mathematical thinking capabilitieswith modified Moore Method of the results learning mathematics basic IIChemistry Education in second semester academic year 2013/2014 is equalto 98,85%. It can be concluded that there is an influence on the mathematicalthinking capabilities by applying Modified Moore Method towards thestudents learning achievement of Basic Mathematic II of Chemistry studyprogram from the FKIP of Universitas Riau in the even semester of2013/2014 academic year.